DIMENSI ETIKA DALAM PRAKTIK BISNIS DALAM PERSPEKTIF GOOD CORPORATE GOVERNANCE (GCG) SYARIAH - Asnawi; Ahyarul Juanda Sagala; Fitra Amar Rosuli; M. Aidil Syahputra; Yabib Fikri Rambe; Ahmad Wahyudi Zein (CV. Barokah Publsiher, 2025)
Business ethics is an essential element in modern business practices, particularly in the implementation of Sharia-based Good Corporate Governance (GCG). This article aims to analyze the dimensions of ethics in business practices, the development of business ethics, principles of professional ethics, business as a noble profession, and the issue of moral relativism in global business. This study employs a literature review method with a qualitative-descriptive approach. The findings indicate that business ethics functions not only as a moral guideline but also as a strategic instrument in ensuring business sustainability. The principles of moral integrity and no harm are universal and remain relevant in addressing global ethical challenges. From the perspective of Sharia-based GCG, business ethics is reinforced by Islamic values such as honesty (shiddiq), justice (‘adl), trustworthiness (amanah), and ihsan, ensuring that business activities are oriented not only toward profit but also toward public welfare and blessings.